If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -1) + x = 11 Reorder the terms: 9(-1 + x) + x = 11 (-1 * 9 + x * 9) + x = 11 (-9 + 9x) + x = 11 Combine like terms: 9x + x = 10x -9 + 10x = 11 Solving -9 + 10x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 10x = 11 + 9 Combine like terms: -9 + 9 = 0 0 + 10x = 11 + 9 10x = 11 + 9 Combine like terms: 11 + 9 = 20 10x = 20 Divide each side by '10'. x = 2 Simplifying x = 2
| 6-9x=6x-9x-6 | | (x^2)+2x+40=(x^2)-x+190 | | 36r^2-1=0 | | 9y-8-6y+7=0 | | -25+55.5+(-29)= | | 6(-3x-3)=5x | | 7x+5x-54=72-6x | | 2c-58=7c-24 | | -15=5b+12-2b+b | | 3x+2+2x-1=6x-20 | | 35.8x+5.90=220.7 | | 17=6z-1 | | 36+(4x-9)=c(2x+1)+25 | | .666=3r | | 18x^2+18y^2-12x+9y+7=0 | | x^2-15x-15=-6x-5 | | -5+-16= | | 2b-8=0.4 | | (4x+7y)+(x-3y)= | | 5-2x=-5-x | | k+(4.21)=19.3 | | 13x+50=180 | | x^2-13x+28=-2x+4 | | -8=6b-14 | | 66.6=3r | | 3e=.75 | | x^2+13x+41=5 | | -(8y+5)-(-7y-7)=2 | | 2g-7g=-24 | | 6x+39=14x-66 | | -2(x-4)=12 | | 7x+3y=6x+5y |